Pemahaman Siswa Terhadap Bahan Ajar Muatan Lokal Bahasa Daerah Jawa Tengah Kelas II SDN 1 Jetis (Uji Coba Bahan Ajar) - Syakban, Ibnu (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This research aims to describe students' abilities in understanding regional language teaching materials in Local Content subjects in class IV of SDN 1 Jetis, Klaten City. The research method used is descriptive quantitative with percentage techniques. The research population was all class II students at SDN 1 Jetis Juwiring Klaten with a sample of 28 class IIB students. The sample was determined using a cluster random sampling technique in the population. The research instrument uses a test sheet. The data analysis technique was carried out using a learning outcomes test which was adjusted to the KKM score for Local Content subjects at SDN 1 Jetis, Klaten City, which was 67. The results showed that 82.1% of students achieved the KKM with an average score of 79.46 . Thus, it can be concluded that students' ability to understand the Klaten regional language is in the good category..